Perfil conceitual a respeito da concepção atomística para os estados físicos da matéria de um grupo de alunos da Educação de Jovens e Adultos - EJA - Menezes, Vanessa Maria Silva (2019)
Educational work based on the conceptual profile allows the teacher and the student to know and respect different ways of seeing the world. According to this theory, the way in which an individual explains a certain phenomenon brings with it epistemological and ontological characteristics that justify such a way of thinking. As far as the study of the atom in the composition of the physical states of matter is concerned, the abstraction required for its understanding and the models used to represent it are some of the characteristics that are not explained by common sense, since it involves a scientific concept . Atomism was chosen because it is a fundamental knowledge to the study of chemistry, since it constitutes the basis for understanding basically all the phenomena to be studied by this science. The present work has proposed to analyze the conceptual profiles regarding the atom in a specific public, with characteristics that differentiate it from the students of the regular education: students of the Education of Young and Adults - EJA. This group of older people, rich life experiences, diversity of social situation and inserted in the world of work was chosen precisely for forming a class not favored by research in the area of the EJA and to have aroused the researcher's interest. Our objective was to analyze the areas of the atom conceptual profile in which these students are found, according to Mortimer (2006), before and after a pedagogical intervention. According to the referential used, the conceptual profile for this concept encompasses different zones, which are the ways of explaining the concept, called realistic, substantialist and atomistic. For that, written activities were carried out and at the end of the process, some of the students were interviewed. The results show us a transition in these zones that walked towards the zone closest to the scientist, considering the existence of empty spaces in the matter and the organization of the particles that compose it. This was expressed in written language, but mainly in non-verbal language, through the use of drawings, and reveals that despite the restricted scientific vocabulary of these students, there was an evolution of concepts and presented in a harmonic way among the areas in which they were classified. The interviews presented data that confirmed the development of a new vision by students that involves scientific terms and models for representing the subject in different physical states, as well as revealing other aspects such as the perception of the plurality of ideas in the classroom by the students and the use of different languages (scientific and common sense) depending on the environment.